Factors Affecting the Transmission of Salmonella by Flies: Natural Resistance to Colonization and Bacterial Interference - Greenberg, Bernard (1970)
Groups of immobilized gnotobiotic houseflies, Musca domestica L., were mono-contaminated with graded doses of Salmonella typhimurium, bicontaminated with S. typhimurium and Proteus mirabilis, and multicontaminated with S. typhimurium and a mouse fecal flora. Of 45 flies fed an average of 22 Salmonella cells alone, 26 showed bacterial multiplication, up to 1.4 × 10(7) in one case. There was a fairly consistent increase in percentage of Salmonella excreters with increasing input, so that all flies given 10(4) and 10(5) cells shed Salmonella some time during an observation period of 8 to 13 days. Multiplication, however, reached higher levels in flies given 10(2) or 10(3) organisms. A high input was not necessary to produce a high proportion of Salmonella excreters. Among 22 flies given an average of 90 Salmonella cells, multiplication occurred in 17 and 18 became excreters. Antagonism between P. mirabilis and S. typhimurium, which was previously described in the blowfly maggot tract, also occurred in the gut of the adult housefly. With an input of 10(3) cells each of Salmonella and Proteus, there was a reduction of Salmonella excreters to 27% on the first day and elimination by the second day. With a normal fecal flora which contained no demonstrable P. mirabilis, 37% of the flies were still excreting Salmonella on the fourth day, but not by day 6; among flies fed Salmonella alone at the same input, the organism was excreted by 87% on the first day and 62% on the second day, and outputs continued for at least 8 days. Salmonella was lodged mainly in the mid- and hindgut 3 days after the infective meal, minimizing transmission through vomit. Comparison studies with the common green bottle fly, Phaenicia sericata Mg., showed it to be more resistant than the housefly to establishment and multiplication of S. typhimurium.